Empowering Financial Literacy and Saving Habits among Students at SMA Islam Sabilurrosyad Gasek Malang through Interactive Financial Education - Burhanuddin Jauhari; Muhammad Lukmanul Khakim (PT. Mifandi Mandiri Digital, 2026)
Financial literacy among adolescents remains relatively low, leading to poor money management practices, limited budgeting skills, and weak saving habits. These challenges were also identified among students at SMA Islam Sabilurrosyad Gasek Malang, highlighting the need for financial education interventions. This community service program aimed to improve students’ financial literacy and promote saving awareness through an interactive educational approach. The program involved 30 students and was implemented through financial literacy training, budgeting simulations, educational games, and group discussions. Program effectiveness was evaluated using pre-test and post-test assessments and participant satisfaction questionnaires. The results showed significant improvements in money management knowledge, understanding of saving, and budget planning skills. The average financial literacy score increased from 62.6 to 85.1, indicating a statistically significant improvement. The findings demonstrate that interactive financial education effectively enhances financial knowledge and encourages positive financial behavior among adolescents. This program contributes a practical model for school-based financial literacy education. Future programs should emphasize the sustainability of financial literacy education through continuous school-based activities and active involvement of teachers and parents in promoting positive financial behaviors among students.